2021
DOI: 10.1111/ibi.12988
|View full text |Cite
|
Sign up to set email alerts
|

Nectar provision attracts hummingbirds and connects interaction networks across habitats

Abstract: Hummingbirds are the main pollinators of a broad diversity of plants in the American continent (Stiles 1978, Zanata et al. 2017, Dalsgaard et al. 2021). These birds are frequent in humanmodified habitats, as they feed on diverse sources of nectar, regardless of whether these are native or artificial/exotic in origin (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…For some species, the installation of feeders in undisturbed habitats is likely to attract additional individuals from a distance, diverting them away from areas they would naturally inhabit (Arizmendi et al 2007). Some hummingbird species are opportunistic rather than specialists, so they exhibit adaptability to disturbed areas (e.g., Ramírez-Burbano et al 2022). Several researchers (Savard et al 2000;Arizmendi et al 2008;Fuller et al 2008) suggest that the use of artificial feeders can influence species distributions, potentially leading to increased richness and/or species displacement.…”
Section: Resultsmentioning
confidence: 99%
“…For some species, the installation of feeders in undisturbed habitats is likely to attract additional individuals from a distance, diverting them away from areas they would naturally inhabit (Arizmendi et al 2007). Some hummingbird species are opportunistic rather than specialists, so they exhibit adaptability to disturbed areas (e.g., Ramírez-Burbano et al 2022). Several researchers (Savard et al 2000;Arizmendi et al 2008;Fuller et al 2008) suggest that the use of artificial feeders can influence species distributions, potentially leading to increased richness and/or species displacement.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, available resources within patches also play a role in determining movement. For example, food resources in human‐disturbed areas may increase connectivity (Ramírez‐Burbano et al 2022), but transformed landscapes do not favour all species equally (Puga‐Caballero et al 2020) and new plant‐pollinator interactions emerge (Marín‐Gómez et al 2022). Our analyses showed that hummingbird seasonality was lower in transformed landscapes compared to natural ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we investigated differences in hummingbird seasonality between ecosystems by testing if natural ecosystem types exhibited greater changes in hummingbird occurrence in comparison to transformed landscapes; and whether humidity, altitude or vegetation type are ecosystem characteristics that influence seasonality. We anticipated that greater changes in hummingbird occurrence would appear in natural ecosystems because urban areas and croplands may provide nectar continuously through bird feeders and ornamental plants (Ramírez‐Burbano et al 2022). Also, humidity, altitude and vegetation type should all affect patterns of plant flowering and in turn predict hummingbird seasonality in different ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas our study system of artificial feeders allowed us to collect behavioral data rapidly, copiously, and efficiently, these behaviors might not necessarily be extrapolated to natural foraging settings. Firstly, the community observed at these artificial feeders is not completely representative of the local natural community (Ramírez‐Burbano et al., 2022). Regarding our focal taxa, there were several hummingbirds observed in the area that did not attend the artificial feeders.…”
Section: Discussionmentioning
confidence: 99%